Molecular basis of Spns1-mediated lysophospholipid transport from the lysosome - Hongwen Chen; Hoa T. T. Ha; Nadia Elghobashi-Meinhardt; Nhung A. Le; Philip Schmiege; Long N. Nguyen; Xiaochun Li (Proceedings of the National Academy of Sciences, 2025)
Spns1 mediates the rate-limiting efflux of lysophospholipids from the lysosome to the cytosol. Deficiency of Spns1 is associated with embryonic senescence, as well as liver and skeletal muscle atrophy in animal models. However, the mechanisms by which Spns1 transports lysophospholipid and proton sensing remain unclear. Here, we present a cryogenic electron microscopy structure of human Spns1 in lysophosphatidylcholine (LPC)-bound lumen-facing conformation. Notably, LPC snugly binds within the luminal-open cavity, where the molecular dynamics simulations reveal that LPC presents a propensity to enter between transmembrane-helices (TM) 5 and 8. Structural comparisons and cell-based transport assays uncover several pivotal residues at TM 5/8 that orchestrate the transport cycle, which are unique to Spns1. Furthermore, we identify a five-residue network that is crucial for proton-sensing by Spns1. Transference of these network residues to Spns2, a sphingosine-1-phosphate uniporter, causes the chimeric Spns2 to be low pH dependent. Our results reveal molecular insights into lysosomal LPC transport and the proton-sensing mechanism by Spns1.